2016
DOI: 10.1186/s40064-016-2400-5
|View full text |Cite
|
Sign up to set email alerts
|

History, problems, and prospects of Islamic insurance (Takaful) in Bangladesh

Abstract: This study explains the history, current problems, and future possibilities of Islamic insurance (takaful) in Bangladesh. To articulate these issues, the researcher has adopted the qualitative method, and data has been collected through secondary sources i.e. articles, books, and online resources. The study reveals that Islamic insurance in Bangladesh is regulated by the Insurance Act 2010 which is contradictory with Islamic insurance causing numerous problems for Islamic insurance. This study also points out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…Additionally, among the less challenging factors, the highest variation is 2.45% that goes to lack of marketing research and the total variation explained by the four moderate challenging factors is 8.84%. Islamic insurance companies in Bangladesh are using traditional methods for insurance policies whereas some of the conventional insurance companies are following modern systems as computerized systems in their operations (Khan et al, 2016),. The clients of Islamic insurance companies are deprived of the convenient use of e-insurance, online business, internet, and computerized system.…”
Section: Pca Of Challenges Of Islamic Insurance Companiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, among the less challenging factors, the highest variation is 2.45% that goes to lack of marketing research and the total variation explained by the four moderate challenging factors is 8.84%. Islamic insurance companies in Bangladesh are using traditional methods for insurance policies whereas some of the conventional insurance companies are following modern systems as computerized systems in their operations (Khan et al, 2016),. The clients of Islamic insurance companies are deprived of the convenient use of e-insurance, online business, internet, and computerized system.…”
Section: Pca Of Challenges Of Islamic Insurance Companiesmentioning
confidence: 99%
“…According to Khan et al (2016), the claim settlement in Bangladesh is a lengthy and timeconsuming procedure. In this study, many respondents agreed that the lengthy procedure in claim settlement hampers the goodwill of the industry.…”
Section: Lengthy Procedures In Claim's Settlementmentioning
confidence: 99%
See 1 more Smart Citation
“…Jehanzeb and Ahmed Bashir (2013) inspect the structure and elements of employee training and development program and later the study present what are the positive outcomes for employees and organizations. Tried to find out the factors affecting the performance of the employee and analysis the effect of the training program Khan, Rahman, Yusoff, and Nor (2016) explain the history, current problems, and future possibilities of Islamic insurance (takaful) in Bangladesh. Sarwar (2016) aims to examine the experience, challenges, and key drives for the growth of the latest progress of the Takaful industry in Bangladesh.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Raja and Kumar (2016) and Islam and Zaman (2013) evaluate the effectiveness of training and development programs in Ashok Leyland Ltd. in India. Khan et al (2016) Job analysis -manpower planning -at the start of the business and as ongoing process performance appraisal -standards, methods, and errors were observed. From the early stage of the 21st century, we found that a remarkable flow surrounded by the businesses to draw and keep hold of the endowment.…”
Section: Literature Reviewmentioning
confidence: 99%